Tekat as a Malaysian heritage : a study of motif, form and meaning / Saemah Yusoff - Yusoff, Saemah (Institute of Graduate Studies, UiTM, 2014)
Tekat is a form of embroidery on cloth, usually velvet, using gold threads whereby shapes and patterns are formed by stitching the gold threads over a core of medium-thickness pre-cut papers (mempulur). It is one of the traditional handicrafts that have been handed down the generations. Today, this Malay art of embroidery still lives on but only in a few locations. Almost all practitioners of tekat tuji are to be found in the royal town of Kuala Kangsar, Perak. Even so, their days are numbered as many are old and often have no heirs to their knowledge. Hence, the art of tekat is facing severe decline if not total extinction. Several reasons are attributed to this phenomenon. Firstly, is the lack of practitioners of tekat.